Environmental analyses to inform transitions to sustainable diets in developing countries: case studies for Vietnam and Kenya - Heller, Martin C.; Walchale, Abhijeet; Heard, Brent R.; Hoey, Lesli; Khoury, Colin K.; Haan, Stef de; Burra, Dharani Dhar; Thi, Thanh Duong; Osiemo, Jamleck; Thi Huong, Trinh; Jones, Andrew D. (Springer, 2020)
Purpose